The emerging landscape of immune checkpoint inhibitor based clinical trials in adults with advanced rare tumors - Arjun Mittra; Naoko Takebe; Vaia Florou; Alice P Chen; Abdul Rafeh Naqash (Taylor & Francis Group, 2021)
"Rare cancers" are a diverse collection of cancers that collectively account for approximately 20% of all adult cancers in the United States. Their rarity has caused an underrepresentation of these cancers in preclinical research and clinical trials, leading to fewer (and often no) treatment options for patients backed by robust clinical evidence. The recent advent of immune checkpoint inhibitors (ICIs) into the oncologist's armamentarium, while revolutionizing the treatment of many common cancers, has also started to make gradual inroads into the treatment of certain rare cancers. One reason is that the efficacy of ICIs depends more on factors intrinsic to the tumor cells and the tumor microenvironment and less on tumor histology. Recent years have seen ICI approvals in many rare cancers, and many trials are being designed using ICIs as single agents or in combination. In this commentary, we present an overview of the emerging role of ICIs in some rare cancers.